Zona Potensial Penyebaran Jaring Insang Dasar (Bottom Gill Net) di Perairan Kepulauan Sangkarrang - Ibnu Malkan Hasbi; Husni Angraeni; Ernawati Ernawati (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
This study aims to determine the potential zone of Millenium Gill Net fishing gear which is scattered in the waters of the Sangkarrang Islands. The research was conducted in April-September 2019 in the waters of the Sangkarrang Islands District with a fishing base location of 5 ° 6'13.2664